Intramedullary Versus Extramedullary Alignment Guide for the Accurate Sagital Tibial Prosthesis Alignment in Total Knee Replacement Arthroplasty - Firas A. Naser (مجلة كلية الطب, 2013)
Background: long term survivorship in total knee arthroplasty is significantly dependant on prosthesis alignment, several studies have correlated poor outcome with malalignment of the components. The debate on the optimal system for femoral alignment is now largely resolved, but there is still controversy about whether intramedullary or extramedullary systems are better for the tibial side.